The effect of extracts of some Organic solvents and crude secondary compounds for some plants in the loss of roles Allatraqueme immature to Musca domestica L. (Diptera: Muscidae) - mohammad Abid falhy, Majeda; Rtha Annon, Mohammed (Al-Qadisiyah Journal of Pure Science, 2018)
Current research includes evaluating the efficiency of some extracts of organic solvents( ethanol , Ethyl acetate and hexane) and crude secondary compounds (alkaloids , phenols and terpenes ) of Citrullus colocynthis L. , Rubus sanctus Shreb and Lycium barbarum L. in some aspects of life of the Musca domestica. The extract ethanol plants tested was the highest impact in the destruction of roles immature insect followed extract hexane then Ethyl acetate , as outweigh R.sanctus in the ratio Almaah for the destruction of eggs reaching 90.00 %, and the highest concentration of 20 mg / ml , compared with control , which amounted % 22.79 night leaf L.barbarum then C.colocynthis reaching 72.31 % , 67.45 % Respectively Moreover, the extracts of organic solvents three recorded the proportion of perdition mentioned Baltrkizalaaly , Regarding the larval stages was 1st Aktherhsasah of larval stages other for all the extracts was the highest rates of destruction of larval stages of the three using the R.sanctus and the highest concentration of 20 mg / ml , where the percentage loss 90.00 % of all larval stages and organic solvents all while its similarity murder rate achieved by extracts ethylacetate for vegetarian Handal and bramble for phases first and second , amounting to 90.00 mg / ml while the (% (85.56 , 56.31) for Tharid phase for C.colocynthis and L.barbarum respectively while the extract in hexane 90.00 % ,81.00 % ,77.84 % , of the mentioned phases , respectively, and the C.colocynthis while the 90.00 % , 65.55 % , 51.20 %, for the L.barbarum same extract and the same focus . As for the effect of extracts of secondary metabolites raw plants tested has achieved extract phenolic compounds raw C.colocynthis highest rate of destruction of the eggs was 85.44 % in the concentration 20 mg / ml , followed by Abstract mentioned plant L.barbarumby loss of 76.44 % and finally the R.sanctus by the destruction of the amount of 63.94 % in the same concentration aforementioned . As for the effect of extracts of vehicles above in the destruction of larval stages of the three has the effect was clear where achieved the highest rates of murder of Atwar larval result of exposure to extract phenolic plants all in concentration 20 mg / ml , as well as with extracts Turbocharger and alkaloid concentration mentioned above except Maabdah larval third of resistance to extract each of the aforementioned vegetable C.colocynthis and L.barbarum where the loss ratios were developed for the mentioned 85.56 % and 69.53 %, respectively .